Lussazioni acromion-claveari - Spinelli, M.S.; Cugnetto, M.; Papalia, M.; Sessa, V. (Lo Scalpello - Journal, 2018)
THE SURGICAL TREATMENT OF ACROMIO-CLAVICULAR DISLOCATION The acromio-clavicular dislocation account approximatively the 10% of the shoulder girdle injury. This lesion is more frequent in male, young and active patients who practice contact sports. Minor grade of dislocations usually remain undiagnosed and this leads to an underestimation of this lesion. The most commonly used classification is the Rockwood’s one that is based on grade of dislocation and ligaments disruption, is divided in 6 grades, from a less severe to a more severe grade. The authors discuss anatomo-pathologic and epidemiologic aspects of the AC dislocation with indication for conservative and surgical treatment.